2015
DOI: 10.3855/jidc.6683
|View full text |Cite
|
Sign up to set email alerts
|

Presence of virulence genes and pathogenicity islands in extraintestinal pathogenic Escherichia coli isolates from Brazil

Abstract: Introduction: Extraintestinal pathogenic Escherichia coli (ExPEC) is associated with various diseases such as urinary tract infections, neonatal meningitis and septicemia. There are many virulence factors (VF) encoded by genes in ExPEC, including papC, papG, ecpA, iroN, fyuA, iutA, ompTp, tsh, hlyF, hlyA and iss. These virulence genes may be present in pathogenicity islands (PAI) or plasmids. Methodology: In this study, we analyzed the presence of VF encoding genes, PAI sequences and phylogenetic groups of 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Studies conducted in Mexico and other countries found that UPEC serogroup strains are integrated mainly in the virulent phylogroups (B2 and D) [17,25,[30][31][32]. In the phylogroup analysis, the PCR-GT-E. coli strains showed a higher frequency of strains in the virulent phylogroups (B2 and D) with significant differences (P < 0.05) when compared with PCR-NGT-E. coli strains.…”
Section: Discussionmentioning
confidence: 88%
“…Studies conducted in Mexico and other countries found that UPEC serogroup strains are integrated mainly in the virulent phylogroups (B2 and D) [17,25,[30][31][32]. In the phylogroup analysis, the PCR-GT-E. coli strains showed a higher frequency of strains in the virulent phylogroups (B2 and D) with significant differences (P < 0.05) when compared with PCR-NGT-E. coli strains.…”
Section: Discussionmentioning
confidence: 88%
“…Besides PAI IV 536 no other PAIs from UPEC 536 were detected in this study. We have shown that EIEC also harbors multiple PAIs as described for UPEC [38]. However, the most predominant combination found in EIEC (PAIs I J96 and II CFT073 ) was not detected in UPEC [35, 38].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that EIEC also harbors multiple PAIs as described for UPEC [38]. However, the most predominant combination found in EIEC (PAIs I J96 and II CFT073 ) was not detected in UPEC [35, 38]. Except for PAI IV 536 the other three PAIs detected in this study did not correlate with the presence of the recognized virulence traits they are reported to encode namely: α-hemolysin, P-fimbriae, Prs-fimbriae, cytotoxic necrotizing factor 1, and aerobactin [35].…”
Section: Discussionmentioning
confidence: 99%
“…Tsh was the first SPATE identified in E. coli [49] and was shown to contribute to the development of respiratory lesions in the air sacs of chickens [22]. The tsh gene is located on ColV-type plasmids, was present in 50% of APEC strains [47], is less commonly associated with human ExPEC, but can be associated with certain human ExPEC strains [18,[50][51][52].…”
Section: Introductionmentioning
confidence: 99%